Bioassessment of Macroinvertebrates in Coban Rais River, Oro-Oro Ombo Vilage, Post Administrative of Batu, Batu City - Adelina do Rego Soares; Sri Sudaryanti; Koderi (Postgraduate, University of Mataram, 2025)
Coban Rais, part of the Brantas River upstream area, is a tourist destination with natural waterfalls and anthropogenic activities affecting its river health. This study analyzed river health using macroinvertebrates sampled at nine stations with varying land uses. Samples were collected with hand nets (500 μm mesh) using a 10-meter kicking technique in riffle areas. Data were analyzed using the SIGNAL2 index. A total of 76 macroinvertebrate families from 15 orders, 3 subclasses, and 1 suborder were identified. Station 4 had the highest diversity (33 families), including Hydropsychidae and Caenidae, while Station 9 recorded the lowest (7 families), including Naididae and Chironomos thummi. SIGNAL2 results categorized stations 1 and 2 as unpolluted (values of 6.26 and 5.39, respectively), stations 3–8 as lightly polluted (values between 3.71 and 4.79), and station 9 as heavily polluted (3.61). Recommendations include maintaining unpolluted stations through regular cleaning and erosion control, reducing waste disposal near lightly polluted stations, and treating livestock waste before discharge at heavily polluted sites. Public awareness campaigns are vital to promote river health and protect macroinvertebrate diversity.